2005
DOI: 10.1002/er.1058
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic optimization of global circulation and climate

Abstract: SUMMARYThe constructal law of generation of flow structure is used to predict the main features of global circulation and climate. The flow structure is the atmospheric and oceanic circulation. This feature is modelled as convection loops, and added to the earth model as a heat engine heated by the Sun and cooled by the background. It is shown that the dissipation of the power produced by the earth engine can be maximized by selecting the proper balance between the hot and cold zones of the Earth, and by optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 17 publications
0
51
0
4
Order By: Relevance
“…For a given rate of entropy production, e.g., in a power plant, the system is designed in a way to maximize the amount of useful work, so that the wasted (thermal) entropy production is minimized. Applied to the atmospheric circulation (Bejan and Reis 2005), this would imply that the entropy production by frictional dissipation is maximized, while the "waste" thermal entropy production is minimized. In this way, it seems that the "constructal law" can be seen as a complement to MEP.…”
Section: Mep and Complex System Theoriesmentioning
confidence: 99%
“…For a given rate of entropy production, e.g., in a power plant, the system is designed in a way to maximize the amount of useful work, so that the wasted (thermal) entropy production is minimized. Applied to the atmospheric circulation (Bejan and Reis 2005), this would imply that the entropy production by frictional dissipation is maximized, while the "waste" thermal entropy production is minimized. In this way, it seems that the "constructal law" can be seen as a complement to MEP.…”
Section: Mep and Complex System Theoriesmentioning
confidence: 99%
“…They showed that beachface slope varies with wave height raised to the power 3/4, and sand grain size raised to the power 4/3. The largest flow system on earth (atmosphere circulation) was also studied from the point of view of the constructal theory [15,16]. The sun-earth-universe assembly was viewed as a power plant, the power output of which is used to force the atmosphere and hydrosphere to flow.…”
Section: Configuration Of Inanimate Natural Flow Systemsmentioning
confidence: 99%
“…The heat balance performed on an infinitesimal latitudinal ring yields the excess heat current q in the ring which is convected towards the poles (the cold sinks) by the Earth's global circulation. The optimisation of the heat current is given by the constructal law (Bejan and Reis, 2005) which requires maximum heat flow at all latitudes. The latitudinal temperature T versus albedo (ρ) variations modulated by the Earth's greenhouse factor (γ) is given by (see Clausse et al (2012))…”
Section: Introductionmentioning
confidence: 99%